Detecting Aquaporin Function and Regulation - Madeira, Ana; Moura, Teresa F.; Soveral, Graça (Frontiers in Chemistry, 2016)
Water is the major component of cells and tissues throughout all forms of life. Fluxes of water and solutes through cell membranes and epithelia are essential for osmoregulation and energy homeostasis. Aquaporins are membrane channels expressed in almost every organism and involved in the bidirectional transfer of water and small solutes across cell membranes. Aquaporins have important biological roles and have been implicated in several pathophysiological conditions suggesting a great translational potential in aquaporin-based diagnostic and therapeutics. Detecting aquaporin function is critical for assessing regulation and screening for new activity modulators that can prompt the development of efficient medicines. Appropriate methods for functional analysis comprising suitable cell models and techniques to accurately evaluate water and solute membrane permeability are essential to validate aquaporin function and assess short-term regulation. The present review describes established assays commonly used to assess aquaporin function in cells and tissues, as well as the experimental biophysical strategies required to reveal functional regulation and identify modulators, the first step for aquaporin drug discovery.